2010
DOI: 10.1590/s0100-736x2010000500012
|View full text |Cite
|
Sign up to set email alerts
|

Anticorpos IgG anti-Neospora caninum e Toxoplasma gondii em búfalas (Bubalus bubalis) criadas no estado do Pará

Abstract: Para determinar a ocorrência de anticorpos IgG anti-Neospora caninum e Toxoplasma gondii em 14 unidades produtivas de búfalos, situadas em 13 municípios no estado do Pará, foram coletadas amostras de soro sanguíneo de 374 fêmeas adultas. Os soros foram submetidos à reação de imunofluorescência indireta (RIFI), utilizando-se os títulos 200 e 64, respectivamente como ponto de corte para N. caninum e T. gondii. Obteve-se 153 (40,9%) de animais soropositivos para N. caninum com 100% das propriedades com focos da i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
14
1
3
Order By: Relevance
“…Previous results in Brazil and other countries have indicated lower prevalence of T. gondii in bovines (no more than 4%, as reported by Huong et al 1998;Gondim et al 1999;Fujii et al 2001 andSilva et al 2010, which is in contrast to the results reported here. The reason for such a discrepancy may be due to the fact that changes in feline populations are occurring in the area under study.…”
Section: Resultscontrasting
confidence: 99%
“…Previous results in Brazil and other countries have indicated lower prevalence of T. gondii in bovines (no more than 4%, as reported by Huong et al 1998;Gondim et al 1999;Fujii et al 2001 andSilva et al 2010, which is in contrast to the results reported here. The reason for such a discrepancy may be due to the fact that changes in feline populations are occurring in the area under study.…”
Section: Resultscontrasting
confidence: 99%
“…In Brazil, N. caninum infection was detected in cattle, sheep, goats, and buffaloes (AGUIAR et al, 2005;VOGEL et al, 2006;VARASCHIN et al, 2011), and in buffalo and cattle, in particular, in the state of Pará (MINERVINO et al, 2007;SILVA et al, 2010). However, there is no record of its occurrence among dairy cattle in the southeast region of this state, which is the most important dairy region (FREITAS, 2001) and new agricultural frontier in the Amazon.…”
Section: Introductionmentioning
confidence: 99%
“…Given that unpasteurized buffalo milk and meat when consumed inadequately cooked from infected animals is a potential source of human toxoplasmosis (Lundén & Uggla 1992, Dehkordi et al 2013. In Brazil, States of the Bahia (Gondim et al 1999), Pará (Silva et al 2010) and São Paulo (Souza et al 2001) found that 3.8% (4/104), 1.1% (4/374) and 49.9% (205/411) of the buffaloes had antibodies to T. gondii respectively, lower results compared to 16.8% (37/220) of the buffaloes reported in this study. Similar results were described in Iran with 14.3% of the buffaloes seropositive to T. gondii (Hamidinejat et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Seroprevalence studies for N. caninum in buffaloes showed a positivity ranging from 1.5% to 70.9% and are described in southeastern and northern region of Brazil (Fujii et al 2001, Gennari et al 2005, Argentina (Campero et al 2007, Konrad et al 2013, Egypt (Dubey et al 1998), India (Meenakshi et al 2007), Vietnam (Huong et al 1998), and Italy (Guarino et al 2000). Seroprevalence to T. gondii are described in Brazil (Silva et al 2010), Argentina (Konrad et al 2013), Vietnan (Huong et al 1998), Iran (Navidpour & Hoghooghi-Rad 1998), and India (Sharma et al 2008) with the seropositivity ranging from 1.1% to 25.4%. Studies showing the seroprevalence for Sarcocystis spp.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation